Cell therapy efficacy and safety in treating tendon disorders: a systemic review of clinical studies - Seyed Peyman Mirghaderi; Zahra Valizadeh; Kimia Shadman; Thibault Lafosse; Leila Oryadi‐Zanjani; Mir Saeed Yekaninejad; Mohammad Hossein Nabian (Journal of Experimental Orthopaedics)
Abstract Purpose Despite substantial animal evidence, cell therapy in humans remains in its infancy. The purpose of this study was to examine the potential therapeutic effects and safety of cell therapy in the treatment of tendon disorders. Methods According to the PRISMA guideline, a systematic review was performed on clinical studies concerning cell therapy in tendon disorders. A comprehensive search including the 5 databases of MEDLINE, Embase, Scopus, Web of Science, and Cochrane Library until December 2021 was carried out and associated with hand searching. The quality of the eligible studies was assessed using the tools suggested by Cochrane recommendations. Qualitative synthesis was performed in 2 tables and discussed separately for rotator cuff, elbow, patella, Achilles, and gluteal tendons. Results Through 6017 records, 22 studies were included in the qualitative synthesis, including 658 patients. All the studies administered autologous cells, except one that used allogenic adipose‐derived mesenchymal stem cells (Allogenic AD‐MSC). Almost all studies demonstrated the safety of cell injection in their follow‐up period with no serious side effects or immunologic reactions, with only a few related minor adverse events in some cases. The included studies showed the effectiveness of cell injection in tendinopathies of different sites, rotator cuff, elbow, patella, Achilles, and gluteal tendons. Among the rotator cuff studies, 4 comparative studies claimed that cell therapy is a more efficient treatment with a lower retear rate and pain level compared to the control group. However, one study found no differences between the groups. No controlled study has been performed on elbow tendinopathies, but 5 case series demonstrated the effectiveness of cell injection in elbow tendon disorders. For Achilles tendinopathies, only one randomized controlled trial (RCT) found that both cell therapy and control groups showed significant pain reduction and functional improvement with no statistical differences at the 6 months follow‐up, but the cell therapy group had improved faster at earlier follow‐ups. Patellar tendinopathy was studied in 2 RCTs, one did not show a significant difference and the other showed superior improvement compared to controls. Conclusion Cell therapy showed promising results and the available evidence suggests that it is safe at several sites of tendon disease. Based on available evidence, cell therapy should be suggested in specific conditions at each site. To approve cell therapy for tendon diseases, randomized clinical trials are required with a large sample size and long‐term follow‐ups. Level of evidence IV